The Pattern of Epistemological Belief in Design among Engineering Students - Daud, Mohd Fadzil; Fuad Khoo, Nur Aini Khoo binti Ahmad; Osman, Sharifah; Wan Hussin, Wan Nazdah Bte; Bin Hanafiah, Khairul Anwar; Zamia Sumeri, Noor Afiqah (International Journal of Learning and Development, 2024)
This study was geared toward identifying the pattern of epistemological belief in design among engineering students enrolled in one of the research universities in Malaysia. To this end, data collection was carried out by employing an adapted instrument of a Likert-type questionnaire with five scales consisting of 68 items. Then, 120 engineering students from several engineering disciplines, such as electrical engineering, mechanical engineering, and civil engineering, were selected from the overall population of Universiti Teknologi Malaysia to determine their epistemological beliefs on design. According to the literature, six dimensions of beliefs were commonly perceived. The students were to describe their beliefs about design knowledge and the nature of knowing and learning design, including the source of knowledge, the certainty of knowledge, structure of knowledge, speed of knowledge acquisition, innate ability of personal and general knowledge, and real-world applicability of knowledge. The study’s findings revealed that the epistemological beliefs of engineering students in each dimension yielded a difference across varying engineering majors.